INOVASI DALAM PENGELOLAAN HUBUNGAN SEKOLAH/MADRASAH DENGAN MASYARAKAT - Kurnia Oktaria; Muhammad Abduh; Karoma Karoma; Mardiah Astuti (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This paper aims to find out what innovations exist in the management of public relations in schools and madrasas. This paper uses the library research method by critically and in-depth examining library materials that are relevant to paper material such as books and journals that are worthy of being used as references.  From the results of the research it is known that the innovations being carried out by Public Relations at this time include using various information technology facilities, such as creating websites, creating several social media accounts, such as YouTube or Instagram.  With these various tools, it is easy for public relations to socialize and introduce various programs and activities in educational institutions.  For example, uploading various extracurricular activities on social media, so that many people can see them.